Accessing Stable Magnesium Acyl Compounds: Reductive Cleavage of Esters by Magnesium(I) Dimers. Issue 56 (6th September 2017) - Boutland, Aaron J.; Lamsfus, Carlos A.; Maitland, Brant; Maron, Laurent; Stasch, Andreas; Jones, Cameron
Abstract: The first examples of magnesium acyls, [(Nacnac)Mgμ‐C(Ph)O(μ‐OR)Mg(Nacnac)] (R=Me, t Bu or Ph; Nacnac=[HC(MeCNAr)2 ] − ; Ar=C6 H2 Me3 ‐2, 4, 6 ( Mes Nacnac), C6 H3 Et2 ‐2, 6 ( Dep Nacnac), C6 H3 i Pr2 ‐2, 6 ( Dip Nacnac)), have been prepared by reductive cleavage of a series of esters using dimeric magnesium(I) reducing agents, [(Nacnac)Mg2 ]. Crystallographic studies reveal the complexes to be dimeric, being bridged by both phenyl‐acyl and alkoxide/aryloxide fragments. The crystal structures, combined with results of spectroscopic and computational studies suggest that the nature of the acyl ligands within these complexes should be viewed as lying somewhere between anionic umpolung acyl and oxo‐carbene. However, reactions of the acyl complexes with a variety of organic electrophiles did not provide evidence of umpolung acyl reactivity. A number of attempts to prepare alkoxide free magnesium acyls were carried out, and while these were unsuccessful, they did lead to unusual products, the crystallographic and spectroscopic details of which are discussed. Abstract : Stable s‐block acyls : The first isolable s‐block metal acyl complexes were readily synthesised through the reductive cleavage of esters using magnesium(I) dimers (see picture). Spectroscopic, crystallographic and computational data suggest that the nature of the bonding within the magnesium‐bound acyl fragments lies somewhere between umpolung acyl and oxo‐carbene in character.